1990
DOI: 10.1159/000186011
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Fixed Charges in the Fenestrated Capillaries of the Mouse Mesentery

Abstract: Previous studies showed the existence of submesothelial fenestrated capillaries in the human parietal and rabbit diaphragmatic peritoneum, as well as in the mouse mesentery. The present study demonstrates the presence of electronegative fixed charges at the luminal aspect of endothelial cells, as well as along the subendothelial basement membrane of the fenestrated capillaries of the mouse mesentery. This situation will eventually preclude the transfenestral passage of anionic plasma proteins. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Gotloib et al provided evidence that anionic sites exist in the normal peritoneum and are found within the mesothelial glycocalyx, subendothelium, and along the basement membrane [124126]. In an experimental model of septic peritonitis whereby rats were administered live E. coli by intraperitoneal injection, a significant reduction in anionic sites at these locations was observed, which was accompanied by increased transperitoneal passage of proteins [85].…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 99%
“…Gotloib et al provided evidence that anionic sites exist in the normal peritoneum and are found within the mesothelial glycocalyx, subendothelium, and along the basement membrane [124126]. In an experimental model of septic peritonitis whereby rats were administered live E. coli by intraperitoneal injection, a significant reduction in anionic sites at these locations was observed, which was accompanied by increased transperitoneal passage of proteins [85].…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 99%
“…In the brain as well as in other organs, vascular endothelial cells contain anionic sites (Rennke et al, 1975;Simionescu et al, 1981;Thurauf et al, 1983;Schmidley and Wissig, 1986;Vorbrodt, 1987;Gotloib et al, 1990). These negative charged sites influence transport of certain macromolecules from blood into the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Ακόμη, μετά από έρευνες των τελευταίων ετών, έχει γίνει πλέον αποδεκτό ότι το περιτόναιο δεν αποτελεί μια απλή, αδρανή, ημιδιαπερατή μεμβράνη αλλά ένα όργανο εκκριτικό και απεκκριτικό [Dobbie JW και συν. 1989-Di Paolo Ν, 1989-Gotloib L, 1990-Dobbie JW, 1990-Di Paolo Ν και συν. 1990(1 ),(2),( 4)].…”
Section: λευκώματαunclassified